Challenges in cancer management and opportunities - Neupane, Prakash Raj (Nepalese Journal of Cancer, 2019)
Cancer Care is a heavily invested and researched area in present context of development of medical science. As the burden of disease is increasing and treatment options are limited, especially in economically deprived regions, this is demanding more viable, modern and cost effective methods for diagnosis and treatment. This is driving to the need of more locally conducted research, more technical collaboration with advanced institutes and of course publishing of high quality data. We are gradually adapting new technology like Liquid based biopsy in diagnostics, targeted/ Immunotherapy in treatment and artificial intelligence in some therapies. These have proven effective and useful but at the huge cost of financial burden. New therapeutic modalities like BMT are emerging and gained importance in recent years. Cancer etiogenesis has heterogeneous components and this disease has very unpredictable biological behavior. Understanding of molecular biology, genetics, gene sequencing has given us tremendous amount of information for prognostics and prediction of treatment methods. Proper explanation and interpretation of so much so of information is very crucial. Clinicians and scientists should be learning and there should be provision for molecular tumor board as well. Slowly but gradually, the new generation care givers of the field of oncology should keep them at the edge of technology and should be able to understand the recent developments to give individualized care to patient and optimal use of available technology to tackle the disease. Writing and publishing in more standard formats is another important issue to be learned so as to communicate with the peers world wide. So we encourage the young oncologists to learn in this regard as well.